Factor Analysis of Professional Training, Social Values, Work Environment, and Gender Roles Towards Career Selection As An Accountant - Hana Angelina; Yanuar Ramadhan (Quantitative Economics and Management Studies, 2023)
This study aims to determine the factors that encourage students' interest in selecting an accountant career in terms of work environment, professional training, social values, and gender roles. This research is expected to provide an overview of the factors that drive a person in selecting the accountant career. This study used a multiple linear method using descriptive analysis through primary data in the form of questionnaires that were distributed to respondents directly. The population in this study employed university students of Esa Unggul University, Trisakti University, Mercu Buana University in the Accounting Study Program with a total sample of 375 respondents. The results of this simultaneous study show that the work environment, professional training, social values, and gender roles are the driving factors in career selection as an accountant career. Partially, the work environment is not a driving factor in career selection as an accountant career, but social values, gender roles, professional training are the driving factors in career selection as an accountant career.